Foundations of Bibliometric Writing: A Comprehensive Guide for Novice Researchers - Sangadji, Suwandi S. (PT. Sangadji Media Publishing, 2023)
In the rapidly evolving landscape of academic research, bibliometrics has emerged as a crucial tool for scholars and researchers, offering a quantitative approach to analyze bibliographic data. This comprehensive guide focuses on empowering novice researchers with a profound understanding of bibliometric writing, covering fundamental concepts, including statistical literature, citation patterns, and publication trends. The guide also explores the use of bibliometrics to identify collaborations, understand metrics like the h-index and impact factor, and enhance research visibility. Practical examples and case studies are provided to facilitate hands-on learning. The first part introduces basic concepts, while subsequent sections delve into publication trends, collaboration identification, and various bibliometric metrics. The guide concludes by emphasizing the transformative potential of bibliometrics, allowing researchers to surpass traditional boundaries, make informed decisions, and contribute meaningfully to their academic fields.